Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Lời giải:
Ta có: \(\lim _{x\to -\infty}\frac{(x^2-1)(1-2x)^5}{x^7+x+3}=\lim_{x\to -\infty}\frac{\frac{(x^2-1)(1-2x)^5}{x^7}}{\frac{x^7+x+3}{x^7}}\)
\(=\lim_{x\to -\infty}\frac{\left ( \frac{x^2-1}{x^2} \right )\left ( \frac{1-2x}{x} \right )^5}{1+\frac{1}{x^6}+\frac{3}{x^7}}=\lim_{x\to -\infty}\frac{\left ( 1-\frac{1}{x^2} \right )\left ( \frac{1}{x}-2 \right )^5}{1+\frac{1}{x^6}+\frac{3}{x^7}}\)
\(=\frac{1(-2)^5}{1}=-32\)
(Nhớ rằng \(\lim_{x\to \infty}\frac{1}{x}=0\) là được )
a) = = -4.
b) = = (2-x) = 4.
c) =
= = = .
d) = = -2.
e) = 0 vì (x2 + 1) = x2( 1 + ) = +∞.
f) = = -∞, vì > 0 với ∀x>0.
a) (x4 – x2 + x - 1) = x4(1 - ) = +∞.
b) (-2x3 + 3x2 -5 ) = x3(-2 + ) = +∞.
c) = = +∞.
d) \(\lim\limits_{x\rightarrow+\infty}\dfrac{\sqrt{x^2+1}+x}{5-2x}=\lim\limits_{x\rightarrow+\infty}\dfrac{\left|x\right|\sqrt{1+\dfrac{1}{x^2}}+x}{5-2x}\)
\(=\lim\limits_{x\rightarrow+\infty}\dfrac{x\sqrt{1+\dfrac{1}{x^2}}+x}{5-2x}\)\(=\lim\limits_{x\rightarrow+\infty}\dfrac{\sqrt{1+\dfrac{1}{x^2}}+1}{\dfrac{5}{x}-2}=-1\).
\(\lim\limits_{x\rightarrow-\infty}\dfrac{\left|x\right|}{x}=\lim\limits_{x\rightarrow-\infty}\dfrac{-x}{x}=-1\)